Transcriptome approach to understand the potential mechanisms of resistant and susceptible alfalfa (Medicago sativa L.) cultivars in response to aphid feeding - Xiong-bing TU; Hai-long ZHAO; Ze-hua ZHANG (Journal of Integrative Agriculture)
Plant breeding for resistance to agricultural pests is an essential element in the development of integrated crop management systems, however, the molecular and genetic mechanisms underlying resistance are poorly understood. In this pilot study, we conducted a transcriptomic analysis of a resistant (R) and susceptible (S) variety of alfalfa, with (+A) or without (–A) aphids (totally four treatments). We used the resistant cultivar Zhongmu 1 and the susceptible cultivar Soca. A total of 3 549 mRNAs were differentially expressed, of which 1 738 up-regulated and 1 307 down-regulated genes were identified in S+A/S–A plants, while 543 up-regulated and 331 down-regulated genes were identified in the R+A/R–A plants. KEGG analysis mapped 112 and 546 differentially expressed genes to 8 and 17 substantially enriched pathways for Zhongmu 1 and Soca, respectively. Six shared pathways were linked to plant resistance traits, including phenylpropanoid biosynthesis associated with salicylic acid synthesis, and linoleic acid metabolism associated with both jasmonic acid and flavonoid biosynthesis. Ultimately, we proposed a preliminary regulatory mechanism of alfalfa cultivar resistance response to aphids feeding based on transcriptome analyses and published documents.